A novel quad-band diversity antenna for LTE and Wi-Fi applications with high isolation - Meshram M.K.; Animeh R.K.; Pimpale A.T.; Nikolova N.K. (My University, 2025)
A novel quad-band diversity antenna is presented with two radiating elements suitable for long-term evolution (LTE) and wireless fidelity (Wi-Fi) applications in handheld devices. The radiating elements are two planar inverted F-shaped antennas (PIFA) constructed by a meandered line and folded patch with interdigitated capacitive strips connected to the folded patch. To achieve high isolation between the two radiating elements, a defected ground plane (a combination of rectangular slot ring and inverted T-shaped slot stub) is employed. The antenna is designed to operate in the 746-787 MHz, 1850-1990 MHz, 1920-2170 MHz, and 3600-3700 MHz frequency bands. The characterization of the antenna in free-space as well as in the proximity of the user head and hand is presented. The results confirm the excellent performance of the proposed diversity antenna. © 1963-2012 IEEE.